Fibroblast based gene banking in pig - Urbán, Martin; Dela Rosa, Ivan Carl; Ecker, András; Benedek, Zsuzsanna; Nagy, Szabolcs Tamás; Bodó, Szilárd; Gócza, Elen (Animal welfare, Ethology and Housing Systems (AWETH), 2023)
Today genetic conservation programs are an essential task for preserving genetic variability. The African swine fever is decimating the European wild boar and domestic pig population, posing a growing threat to native species. These animals have lower population numbers than the species used by the meat industry, so a pandemic like this poses a more significant threat. One of these pig species is “Keszthelyi Large White”. This is a unique breed to Keszthely University, and the current pandemic endangers it. We isolated adult porcine fibroblast from ear tissue samples from 25 sows. The tissue samples were cultured in an adult fibroblast medium containing Knockout F12 DMEM. The fibroblasts were cultured in a CO2 incubator at 37.50 Celsius and 5% CO2. After 15 days of culture, the cultures were gathered in cryotubes with individual barcodes. The samples were stored at -1500C. We collected DNA and RNA samples from the cultures for later analyses. We also tested viability before and after freezing on cultures with Arthur Fluorescent Cell Counting Machine. Viability in cell cultures was, on average, 97%. We took samples from the cell cultures and immunostained the samples detecting titin and actin. The protocol developed by our group may pave the way for the proper isolation and culture of porcine fibroblasts to use it for further research. iPSCs from pigs can be used in various approaches. Since the pig’s anatomical system is being studied with relation to human medicine for organ replacement and other medical purpose.